p38 MAPK alpha mediates cytokine-induced IL-6 and MMP-3 expression in human cardiac fibroblasts - Sinfield, John K. (Academic Press, 2013)
Pre-clinical studies suggest that the p38 MAPK signaling pathway plays a detrimental role in cardiac remodeling, but its role in cardiac fibroblast (CF) function is not well defined. We aimed to identify the p38 MAPK subtypes expressed by human CF, study their activation in response to proinflammatory cytokines, and determine which subtypes were important for expression of specific cytokines and matrix metalloproteinases (MMPs). Quantitative real-time RT-PCR analysis of mRNA levels in human CF cultured from multiple patients revealed a consistent pattern of expression with p38α being most abundant, followed by p38γ, then p38δ and only low expression of p38β (3% of p38α mRNA levels). Immunoblotting confirmed marked protein expression of p38α, γ and δ, with little or no expression of p38β. Phospho-ELISA and combined immunoprecipitation/immunoblotting techniques demonstrated that the proinflammatory cytokines IL-1α and TNFα selectively activated p38α and p38γ, but not p38δ. Selective p38α siRNA gene silencing reduced IL-1α-induced IL-6 and MMP-3 mRNA expression and protein secretion, without affecting IL-1α-induced IL-1β and MMP-9 mRNA expression. In conclusion, human CF express the α, γ and δ subtypes of p38 MAPK, and the α subtype is important for IL-1α-induced IL-6 and MMP-3 expression in this cell type.